2022
DOI: 10.1161/strokeaha.121.035494
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Motor Skill Learning in Acute Stroke Patients Without Lesions to the Thalamus and Internal Capsule

Abstract: Background: It is currently unknown whether motor skill learning (MSkL) with the paretic upper limb is possible during the acute phase after stroke and whether lesion localization impacts MSkL. Here, we investigated MSkL in acute (1–7 days post) stroke patients compared with healthy individuals (HIs) and in relation to voxel-based lesion symptom mapping. Methods: Twenty patients with acute stroke and 35 HIs were trained over 3 consecutive days on a neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…This finding indicates that stroke survivors have online motor learning deficits when compared with neurologically intact adults, which agrees with some prior studies 27,28 but differs to some extent from other existing motor learning literature. [14][15][16][17]29 It is likely that this divergence from previous literature results from our examination of mildly impaired individuals using a multi-DOF, functionally relevant motor acuity task during gait. For example, recent research suggests that reinforcement learning was impaired early after the stroke but not in the chronic phase, whereas error-based learning was unaffected after stroke at either time point when compared with controls.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This finding indicates that stroke survivors have online motor learning deficits when compared with neurologically intact adults, which agrees with some prior studies 27,28 but differs to some extent from other existing motor learning literature. [14][15][16][17]29 It is likely that this divergence from previous literature results from our examination of mildly impaired individuals using a multi-DOF, functionally relevant motor acuity task during gait. For example, recent research suggests that reinforcement learning was impaired early after the stroke but not in the chronic phase, whereas error-based learning was unaffected after stroke at either time point when compared with controls.…”
Section: Discussionmentioning
confidence: 75%
“…For example, some studies suggest that stroke primarily affects the processes underlying motor control and execution, while leaving the learning of motor skills intact. [14][15][16][17] However, a recent study revealed that the extent of motor learning deficits following a stroke is dependent on the severity of motor impairment. 18 It is important to note that a major challenge in establishing evidence of learning deficits is that performance deficits can be misinterpreted as learning deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the potential for recovery varies between chronic and non-chronic stroke cases. The optimal recovery period is within 3 months after stroke, particularly within 4 weeks of its onset ( 47 ). Therefore, when selecting rTMS parameters, it is crucial to consider the different stroke stages and hemiplegia severities in order to develop individualized rehabilitation programs in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Byblow et al ( 12 ) have further suggested that acute stroke patients show ~70% resolution of motor impairment if corticospinal tracts are functional. Overall, neuroimaging studies have confirmed that amount, connectivity, and neurophysiologic function of CST is related to impairment and functional recovery post-stroke ( 13 16 ).…”
Section: Introductionmentioning
confidence: 90%